Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.0735-2166.2005.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Urban Interests and Campaign Contributions: 
Evidence from Los Angeles

Abstract: Political activity is a key determinant of group influence in urban politics. This article examines a form of political activity often ignored by urban scholars, namely, campaign contributions. Using data from the 2001 Los Angeles municipal elections, I explore contributions from various urban interests. Because of its ability to overcome collective action problems, I expect business to be the main contributors, and among corporate interests, I expect development concerns to predominate. Although business cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…These sectors did not dominate fundraising (although they were quite active), and there is no indication that any other sector did either. There is no group of businesses that provide most of the funds to local candidates, a finding consistent with past research by Krebs (2005) and Fleischmann and Stein (1998). There were over 120,000 contributions worth over $67 million (excluding candidate personal funds and independent expenditures) during these five elections, but few contributors gave over $30,000 total 11 .…”
Section: Evaluating the Three Fundraising Modelssupporting
confidence: 81%
See 1 more Smart Citation
“…These sectors did not dominate fundraising (although they were quite active), and there is no indication that any other sector did either. There is no group of businesses that provide most of the funds to local candidates, a finding consistent with past research by Krebs (2005) and Fleischmann and Stein (1998). There were over 120,000 contributions worth over $67 million (excluding candidate personal funds and independent expenditures) during these five elections, but few contributors gave over $30,000 total 11 .…”
Section: Evaluating the Three Fundraising Modelssupporting
confidence: 81%
“…They also found that fundraising patterns varied in the two cities, with St. Louis candidates relying more heavily on small contributions rather than a handful of large contributions, as was evident in Atlanta. Research on Los Angeles has uncovered the same pattern that exists in Atlanta and St. Louis: business interests dominate but many different sectors of the business community are active in financing campaigns (Krebs, 2005).…”
mentioning
confidence: 96%
“…Occasionally, we catch an undeveloped glimpse of the possible significance of other "groups" that might (or might not) reflect some of the cultural groupings suggested here-as in the participation of religious and nonprofit donors to Harold Washington's mayoral campaigns (Krebs and Pelissero 2001). But taken as a whole, the existing research on voting in local elections would seem to suggest that election outcomes in U.S. cities are mostly driven by race/ ethnicity on one hand and the campaign contributions of business interests on the other hand (Krebs 2005), except perhaps in the special case of San Francisco where the political empowerment of gays is important (DeLeon 1992;Bailey 1999). Matters of religiosity and the broader cultural divisions outlined earlier are largely ignored.…”
Section: The Culture War Debate and A Reinvigorated Study Of Local Elmentioning
confidence: 82%
“…According to Fleischmann and Stein's (1998) study of contributions to local candidates in St. Louis and Atlanta, business and the legal community were the primary donors in these contests followed by donations from the development community (e.g., commercial/ residential developers, property management, real estate, title firms, construction and contracting, planning, architecture, and engineering interests). Krebs (2005) found that corporate interests dominate campaign contributions in Los Angeles city elections, but not all corporate interests are equally active. Within the corporate community, professional and development interests are most active, followed by several different corporate interests (entertainment, financial, retail/services, miscellaneous business), and manufacturing and transportation/ public works concerns.…”
Section: Campaign Financementioning
confidence: 99%